DCOTECH water level system / Mazratul Firdaus Mohd Zin, Fatimah Nur Mohd Redzwan and Farid Zuhri Kamal - Mohd Zin, Mazratul Firdaus; Mohd Redzwan, Fatimah Nur; Kamal, Farid Zuhri (2017)
This paper presents the DCOTECH water level control system which monitors the water level of a tank. Water level management approach would help in reducing water overflow and possibility of flash floods. The reservoir provided is one of a preventive action to prevent flood. The DCOTECH water level system is a warning system for residents to be more prepared whenever flood is approaching. A prototype of the DCOTECH water level system has been constructed and it resembles a miniature dam or reservoir with installed system. The system automatically switches OFF the motor which controls the drainage valve once the tank is empty. The valve is switched ON whenever the tank is FULL. DCOTECH water level system uses the microcontroller for water level sensing and control. The microcontroller could detect the water level and stated as low, average, and high level. Each level is indicated with three different LEDs. When the water level is low, a green led will light up, yellow led turns ON when the water is at average level and red led will light up when the water level is high.